Translation Processes in the Translation Training Programme of the DRC - Ambroise Lumbala Lumbala (Ziglôbitha, 2024)
Abstract: More studies are being conducted in the didactics of translation to find out what it can consist of and how it can be achieved. This paper evaluates the translation training programme of the DRC in order to point out the conceptualisation of the translation processes, in particular the controlled ones of comprehension and re-expression. It is basically a library research. The results tend to indicate that more weight is given to re-expression than to comprehension. Given that production is dependent on comprehension, I suggest that attention of equal par should be given to both these phases of translation.